Central African Republic : Poverty Reduction Strategy Paper; Preparation Status Report. (IMF Staff Country Reports; Country Report, 2007)
This Status Report discusses preparation of the Poverty Reduction Strategy Paper (PRSP) on Central African Republic. The government has decided to design an interim strategy (the Economic and Social Policy Framework Document - Document cadre de politique economique et sociale-DCPES) while waiting for the PRSP to be finalized. Multiyear macroeconomic projections and the annual fiscal framework will match resource allocations with PRSP objectives and programs. The PRSP will be implemented in a stable macroeconomic policy framework, and medium-term expenditure management will focus on poverty reduction and economic recovery.